2012
DOI: 10.1371/journal.pone.0053039
|View full text |Cite
|
Sign up to set email alerts
|

Comparable High Rates of Extended-Spectrum-Beta-Lactamase-Producing Escherichia coli in Birds of Prey from Germany and Mongolia

Abstract: Frequent contact with human waste and liquid manure from intensive livestock breeding, and the increased loads of antibiotic-resistant bacteria that result, are believed to be responsible for the high carriage rates of ESBL-producing E. coli found in birds of prey (raptors) in Central Europe. To test this hypothesis against the influence of avian migration, we initiated a comparative analysis of faecal samples from wild birds found in Saxony-Anhalt in Germany and the Gobi-Desert in Mongolia, regions of dissimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
85
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 44 publications
7
85
0
Order By: Relevance
“…However, our study revealed a higher occurrence among kelp gulls in accordance with studies regarding Brown-headed gulls and Franklin's gulls (5). Although the resistance gene families described in this study are similar to those reported previously (2,4,5,12,(14)(15)(16)(17)(18)(19), we documented for the first time the presence of bla SHV-2A and the predominance of bla CTX-M-2 among wild birds. The latter mirrors the situation observed for nosocomial infections in Argentinian hospitals (20,21), confirming the endemicity of bla CTX-M-2 within this area and its potential transmission from humans to wild birds and/or vice versa.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…However, our study revealed a higher occurrence among kelp gulls in accordance with studies regarding Brown-headed gulls and Franklin's gulls (5). Although the resistance gene families described in this study are similar to those reported previously (2,4,5,12,(14)(15)(16)(17)(18)(19), we documented for the first time the presence of bla SHV-2A and the predominance of bla CTX-M-2 among wild birds. The latter mirrors the situation observed for nosocomial infections in Argentinian hospitals (20,21), confirming the endemicity of bla CTX-M-2 within this area and its potential transmission from humans to wild birds and/or vice versa.…”
supporting
confidence: 91%
“…Several studies have documented the occurrence of ESC r Enterobacteriaceae isolates among wild birds at prevalences ranging from 0% to 37% (4,(11)(12)(13)(14)(15). However, our study revealed a higher occurrence among kelp gulls in accordance with studies regarding Brown-headed gulls and Franklin's gulls (5).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Human isolates of CTX-M-producing E. coli ST648 have been reported from various geographical regions, such as Europe, North and South America, Africa, and Asia; the majority of these isolates belong to phylotype D (22)(23)(24)(25). CTX-Mproducing E. coli ST648 strains have also been isolated from wild birds in Mongolia and Germany (24,(26)(27)(28) and from companion and livestock animals in European countries (24,29,30). A recent study on ESBL-producing E. coli isolates (n ϭ 1,152) sampled in Europe, predominantly from dogs, cats, and horses, identified 40 (3.5%) ESBL-producing E. coli strains as ST648 (phylotype D, CTX-M-15 positive; 72.5%), whereas ST131 isolates (phylotype B2, CTX-M-15-positive; 46.9%) occurred less frequently (2.8%) (30).…”
Section: Discussionmentioning
confidence: 99%
“…Although the ST38 and ST648 groups originated mainly from humans, hospitalized patients accounted for 36.8% (7/19) of isolates in the ST648 group compared with 18.8% (3/16) in the ST38 group. ST648 isolates possessing ␤-lactamases have been identified worldwide (40,42,46), suggesting that ST648 ESBLs may contribute to the spread of the ␤-lactamase gene and that these isolates may be more likely than others to cause extraintestinal infections, ultimately resulting in multidrug resistance.…”
Section: Discussionmentioning
confidence: 99%